Subjective strategies for small business growth: An evaluation of the causal maps of small independent retailers - Jenkins, Mark (Cranfield University, 1995)
This study concerns the issue of small business growth. It has been widely established that small business growth is important to a region, both economically and socially, most notably through the generation of employment. However, a number of studies have revealed that only a small proportion of small businesses generate this growth. There is a lack of understanding concerning the reasons why some small businesses grow and others do not. This study considers the subjective strategies of small business owner-managers as a basis for drawing comparisons between growers and non-growers. A causal mapping methodology is used to represent subjective strategy. These causal maps provide a representation of how individual owner-managers see the development of their business. A series of propositions, developed from the existing literature, provide an indication of the characteristics which may discriminate between growth and non-growth oriented owner-managers. These propositions allow for the comparison of the causal maps which are elicited from thirty owner-managers of independent retail businesses. The thirty respondents are grouped into comparative categories based on growth and non-growth intentions and behaviours. The evaluation of these propositions indicates that the owner- managers of growing businesses hold subjective strategies that are more coherent, and include a greater proportion of performance measures than their non-growth oriented counter parts. The maps of non-growth oriented owner-managers show a greater proportion of concepts relating to control and the individual's personal needs and values.